Polyploid species rely on vegetative reproduction more than diploids: a re-examination of the old hypothesis - Herben, Tomáš; Suda, Jan; Klimešová, Jitka (Annals of botany, 2017)
BACKGROUND AND AIMS: Polyploidy is arguably the single most important genetic mechanism in plant speciation and diversification. It has been repeatedly suggested that polyploids show higher vegetative reproduction than diploids (to by-pass low fertility after the polyploidization), but there are no rigorous tests of it. METHODS: Data were analysed by phylogenetic regressions of clonal growth parameters, and vegetative reproduction in culture on the ploidy status of a large set of species (approx. 900) from the Central European Angiosperm flora. Further, correlated evolution of ploidy and clonal traits was examined to determine whether or not polyploidy precedes vegetative reproduction. KEY RESULTS: The analyses showed that polyploidy is strongly associated with vegetative reproduction, whereas diploids rely more on seed reproduction. The rate of polyploid speciation is strongly enhanced by the existence of vegetative reproduction (namely extensive lateral spread), whereas the converse is not true. CONCLUSIONS: These findings confirm the old hypothesis that polyploids can rely on vegetative reproduction which thus may save many incipient polyploids from extinction. A closer analysis also shows that the sequence of events begins with development of vegetative reproduction, which is then followed by polyploidy. Vegetative reproduction is thus likely to play an important role in polyploid speciation.
Keywords: Magnoliopsida; Diploidy; Genetic Speciation; Phylogeny; clonal traits; phylogenetic analysis; polyploidy; vegetative reproduction; correlated evolution; Polyploidy; diploidie; vznik druhů (genetika); fylogeneze; polyploidie